Multilingüismo en la traducción de Zeru horiek (1995) de Bernardo Atxaga al finés y al estonio - Merilin Kotta (Interlitteraria)
Multilingualism in the Translation of Bernardo Atxaga’s Zeru Horiek (1995) into Finnish and Estonian. Zeru horiek (1995, The Lone Woman, English translation by Margaret Jull Costa) is the second most multilingual novel written by Bernardo Atxaga after Obabakoak. While Basque is the source language of his literary works, his fictional world is multilingual. In Zeru horiek seven natural languages appear together with Basque: English, Spanish, French, Italian, Catalan, Galician and Latin. This paper investigates how and why these languages are used in the novel, based on the theoretical approaches presented by Manterola (2019) and Verschik and Saagpakk (2023). Another purpose is to bring into the spotlight two translations of the novel never studied before: the Finnish version Tuolla taivaalla (1999, translated by Tarja Roinila) and the Estonian version Need taevad (2022, by the author of this article). Twenty-three years separate these translations, but the literary contexts of their publication are not very different. Firstly, because of the dominance of English as a main source language of literary translations, and secondly, on account of the fact that Basque, Latin and Romance language skills are not very common in its target readers.